Business models for sustainability in living labs - Burbridge, M.; Morrison, Greg; van Rijn, M.; Silvester, S.; Keyson, D.; Virdee, L.; Baedeker, C.; Liedtke, C. (2016)
© Springer International Publishing Switzerland 2017.There are an estimated 170 active living labs across the globe. All have common elements but not all of them contribute to the delivery of sustainable living. Here we consider the business models of sustainability in living labs (SusLabs). Specifically we review four active living laboratories that are part of the SusLab North West Europe network. We show that the business cases are different for at least two reasons. One is that each SusLab project has a specific focus even though all are seeking to develop energy efficient innovative products, services or systems. Examples of focus include demonstration projects, knowledge generation through research and business to business development. The other is that each came about for different reasons which might include significant public or private sponsorship, or through academia-business co-creation, and this too is reflected in the business case. We also show that the business cases are not static, but may evolve over time as opportunities are created and as partners develop a clearer understanding of the potential of each SusLab. We propose that, based on a common definition of a SusLab, theoretical considerations and societal needs, as well as insights from the cases, it should be possible to build a business case for a SusLab which draws on knowledge rather than learning-by-doing.